Biological Activity of a 4-Hydroxy-Furanyl-Benzamide Derivative on Heart Failure - Lauro, Figueroa-Valverde; Marcela, Rosas-Nexticapa; Maria, López-Ramos; Magdalena, Alvarez-Ramirez; Virginia, Mateu-Armad Maria; Francisco, Díaz-Cedillo; Catalina, Cervantes-Ortega; Montserrat, Melgarejo-Guutierrez (Drug Research, 2022)
Background There are studies that suggest that some benzamide derivatives may exert effects on heart failure; however, their molecular mechanism is not very clear.Objective The aim of this research was to evaluate the biological activity of a 4-hydroxy-furanyl-benzamide derivative against heart failure translated as area infarct.Methods Biological activity produced by 4-hydroxy-furanyl-benzamide derivative against heart failure was determinate using an ischemia-reperfusion injury model. In addition, the effects exerted by the 4-hydroxy-furanyl-benzamide derivative on left ventricular pressure (LVP) was evaluated in the absence or presence of some drugs such as yohimbine, butaxamine, methoctramine and L-NAME using a model of rat heart isolated.Results The results showed that 4-hydroxy-furanyl-benzamide derivative decrease both infarct area and LVP. However, the effect produced by 4-hydroxy-furanyl-benzamide derivative on LVP was inhibited in the presence of both methoctramine and L-NAME.Conclusions All these data suggest that biological activity produced by 4-hydroxy-furanyl-benzamide derivative on left ventricular pressure is through of both M2-muscarinic receptor and nitric oxide synthase enzyme activation. It is important to mention that this phenomenon results as a decrease of both infarct area and heart failure.
Keywords: 4-hydroxy-furanyl-benzamide; infarct area; heart failure; M2-muscarinic receptor.